Peran Customer Experience, Loyalty Program, dan E-Service Quality Terhadap Repurchase Intention Gopay Melalui Customer Satisfaction Pada Gen Z Semarang - Amalia Annisa Dwiana; Lutfi Nurcholis (Komunitas Dosen Indonesia, 2025)
This study aims to examine the influence of customer experience, loyalty programs, and digital service quality on repurchase intention among Gopay users, with customer satisfaction acting as an intervening variable. A quantitative method was employed using a survey approach with questionnaires distributed to respondents. The sample consisted of 96 Generation Z users of Gopay in Semarang City, selected using a non-probability purposive sampling technique. Data analysis was conducted using SPSS software. The results indicate that customer experience, loyalty programs, and e-service quality each have a positive and significant effect on repurchase intention. Furthermore, customer satisfaction was found to significantly mediate the relationship between the three independent variables and repurchase intention. These findings highlight the critical role of customer satisfaction in enhancing the impact of experience, loyalty initiatives, and digital service quality on user behavior. For digital wallet services like Gopay, focusing on improving customer satisfaction can lead to stronger consumer loyalty and an increased likelihood of continued usage.